2019
DOI: 10.37358/rc.19.1.6840
|View full text |Cite
|
Sign up to set email alerts
|

Complex Compounds of Sm(III) with Chlorhexidine Synthesis, characterization, luminescent properties and antibacterial activity

Abstract: Three new samarium(III) complex compounds with chlorhexidine as ligand and mixed ligands chlorhexidine/o-phenanthroline have been prepared and characterized by elemental and thermogravimetrical analyses, infrared, electronic and luminescence spectra. The complexes corresponded to the formulas: [Sm(CHX)(NO3)2]� NO3, [Sm(CHX)(o-phen)2]� (NO3)3 and [Sm2(CHX)(o-phen)2(NO3)4]�(NO3)2, where CHX was the chlorhexidine. Chlorhexidine acted as neutral tetradentate NNNN donor, coordinating through the four imine nitrogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 15 publications
(16 reference statements)
1
4
0
Order By: Relevance
“…The results of in vitro antimalaria of 2 showed that this compound exhibits very high activity against Plasmodium, giving an IC50 value of 0.3 µg/mL (5.976 x 10 -7 M), and this is comparable with the control positive chloroquine with an IC50 value of 3 x 10 -7 M. This value is stronger than the antimalarial drug from the organotin (IV) compound, which has been reported lately [9,10,16] and may be better than other synthetic compounds having antimalarial activity which have been reported by others [17][18][19][20]. The data of activity test can be seen in Figure 8 and Table 2, while the data for the chloroquine are in Figure 9.…”
Section: In Vitro Antimalarial Of Artonin M (2)supporting
confidence: 52%
“…The results of in vitro antimalaria of 2 showed that this compound exhibits very high activity against Plasmodium, giving an IC50 value of 0.3 µg/mL (5.976 x 10 -7 M), and this is comparable with the control positive chloroquine with an IC50 value of 3 x 10 -7 M. This value is stronger than the antimalarial drug from the organotin (IV) compound, which has been reported lately [9,10,16] and may be better than other synthetic compounds having antimalarial activity which have been reported by others [17][18][19][20]. The data of activity test can be seen in Figure 8 and Table 2, while the data for the chloroquine are in Figure 9.…”
Section: In Vitro Antimalarial Of Artonin M (2)supporting
confidence: 52%
“…Alexander Fleming highlighted the importance of chemistry research in designing and modifying molecules to develop new drugs or to enhance the properties of the existing ones [9,[49][50][51]. After decades, in the context of antimicrobial resistance this is more necessary than ever [9].…”
Section: Figure 6 Distribution Of Antimicrobial Resistance Accordingmentioning
confidence: 99%
“…Their coordination ability is determined by their structural features, namely a planar heteroaromatic system with two nitrogen atoms which permit the formation of a chelate with the metal ion [9,10]. The literature comprises papers in which phen and bipy are used as coligand in the obtaining of metal complexes which have applications in chemistry, biology and medicine [11][12][13][14][15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%